Hubungan Lama Menjalani Hemodialisis dengan Efikasi Diri pada Pasien yang Menjalani Hemodialisis: Hubungan Lama Menjalani Hemodialisis dengan Efikasi Diri pada Pasien yang Menjalani Hemodialisis - Aulia Fahmi Alfarizi; Taufan Arif; Sulastyawati; Naya Ernawati (Jurnal Keperawatan Terapan, 2026)
Abstract: Introduction: Self-efficacy plays a crucial role in the success of therapy because it is related to patients’ confidence in adhering to treatment. Consequently, low self-efficacy may result in suboptimal treatment adherence. During the initial phase of hemodialysis, patients commonly experience difficulties in adapting, but this adaptive ability tends to improve as they gain more experience and understanding of the therapy. Objective: This study aims to examine the relationship between the duration of hemodialysis treatment and self-efficacy among hemodialysis patients. Methods: A quantitative correlational design with a cross-sectional approach was employed. The study sample consisted of 100 hemodialysis patients selected through purposive sampling. The independent variable was the duration of hemodialysis, while the dependent variable was self-efficacy. Self-efficacy was measured using the General Perceived Self-Efficacy questionnaire, and patient medical records were used to determine the duration of hemodialysis. Data analysis was performed using the Spearman Rank correlation test. Result: The results indicated a significant relationship with moderate strenght between the duration of hemodialysis and self-efficacy, with a p-value of 0.000 and a correlation coefficient of 0.448. Conclusion: These findings suggest that the longer patients undergo hemodialysis, the higher their self-efficacy levels. A longer duration of hemodialysis allows for the accumulation of experience and information from healthcare professionals and fellow patients, which contributes to enhanced cognitive functioning. This cognitive improvement supports patients’ understanding, adaptation, and coping abilities, thereby increasing their confidence in managing therapy as reflected in improved self-efficacy.